TESTES DE GERMINAÇÃO E VIGOR EM SEMENTES DE FEIJÃO IRRIGADO - CULTIVAR TAA DAMA - Castro Marçal Müller , Yasmin; da Silva Lopes , Adriano; da Silva Franco , Jhonatan; Gomes Miranda , Roger; Vitor Oliveira Klip , Dioph; Oliveira Pimenta Couto , Caio (ANAIS DO ENIC, 2026)
-